Spectroscopic, DFT, anti-bacterial, and in-silico investigations of novel semicarbazone and thiosemicarbazone synthesised from asymmetrical chalcones - Nikita Sharma; Har Lal Singh (Next Materials)
Antimicrobial drugs that target human pathogenic bacteria and fungi include derivatives of thiosemicarbazone and semicarbazone. This work was intended to explore the novel antibacterial agents derived from thiosemicarbazone and semicarbazone derivatives in the light of these potential agents. Ten derivatives of the unsymmetrical chalcone thiosemicarbazone and semicarbazone were synthesised at room temperature. After that the synthesis compounds were investigated using elemental analysis, melting point, UV, IR, 1H-, 13C-NMR spectroscopy and mass spectrometry. Later, computational tools were utilised for evaluating pharmacological attributes such as bioavailability score, Lipinski rule, absorption, distribution, metabolism, excretion and toxicity. Also, density functional theory (DFT) was used to compute quantum computations such as HOMO, LUMO, and chemical descriptors. Finally, molecular docking was performed against two dangerous bacteria (Bacillus subtilis and Escherichia coli). Based on the docking score and binding affinity calculation, these derivatives were found to have a greater affinity than standard antibiotics against selected the pathogens. Based on the computational details, it may be determined to do an in-vitro test for antibacterial activity against B. subtilis and E.coli. Through resulting antibacterial activity, results were compared to standard medications and it was discovered that a couple of synthesized compounds had nearly the same value as standard drugs. The pharmacokinetics, drug-likeness, and physicochemical characteristics were predicted by the SwissADME software. The findings suggested that thiosemicarbazones and semicarbazones possess favorable interaction patterns and binding energies. The biological capacity of each molecule to inhibit bacterial strains exhibited variability in the evaluation of the compounds' in vitro antibacterial efficacy. Thus, synthesized compounds may function as a potential target for bacterial agents. Based on the results obtained, future work will focus on selected compounds for the synthesis of metal complexes and their in-vivo investigations.